HEALING RECOGNITION SYSTEM IN DIGITAL IMAGE USING FUZZY ASSOCIATIVE MEMORY METHOD - Muammar Alzaky; Mukti Qamal; Fadlisyah Fadlisyah (TECHSI - Jurnal Teknik Informatika, 2019)
AbstractMuslim culture introduces the tradition of calligraphy as a form of Islamic art that uses the verses of the Qur'an as the main focus of recognition in the Islamic tradition. Concludes with the development of knowledge that the Khat tradition has been developed with technology. Detection of Khat with the Fuzzy Associative Memory method to detect patterns on the Khat by detecting an image or a photograph. And in pedektisian in the picture can be implanted prior training patterns in order to recognize the Khat pattern. Keywords: Islamic Calligraphy Khat, Khat Introduction, Fuzzy Associative Memory